Combretum-Terminalia vegetation accumulates more carbon stocks in the soil than the biomass along the elevation ranges of dryland ecosystem in Southern Ethiopia. (August 2018) - Tesfaye, Musse; Negash, Mesele
Abstract: Dry land ecosystems including Combretum-Terminalia vegetation cover a wider area in the tropics. These resources are believed to greatly contribute for climate change mitigation in dry land ecosystems. Therefore, the objective of this study was to investigate biomass and soil carbon stocks of Combretum-Terminalia vegetation along the elevation ranges. A total of 60 nested sample plots of 20 m × 20 m were laid systematically along lower, middle and higher elevation ranges, representing 20 plots for each elevation. Within each nested sample plot inventory of woody species, litter and soil samples (0–15, 15–30 cm layers) were collected. The total carbon stocks (biomass plus soil) significantly (p < 0.05) differed among the three studied elevation ranges. The biomass carbon stocks were not significantly different between middle and higher elevations but both of them significantly (p < 0.05) differed from lower elevation, and also showed a decreasing trend from lower to higher elevations. However, inconsistence trends were observed for soil organic carbon and litter along the elevation ranges. It was concluded that woodland ecosystem has a potential to accumulate higher carbon stocks in the soil than the biomass and significantly vary along elevations. Highlights: Combretum-Terminalia woodland ecosystem sinks high C stocks both in the biomass and soil along an elevation gradient than some other dryland vegetation reported in Ethiopia. Soil contributed above 67% of the total woodland ecosystem C stocks across the three elevations. Among the tree species recorded, Acacia bussei and Combretum molle, contributed high proportion of C stock of the total biomass C stocks along the elevation gradient.